2006
DOI: 10.1111/j.1537-2995.2006.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with parameters of engraftment potential of umbilical cord blood

Abstract: UCB banks should emphasize selecting the heaviest infants and processing large-volume units with high NCCs to optimize hematopoietic potential. Minority recruitment should be encouraged with consideration given to inherent racial differences in cell counts. There does not appear to be a significant relationship between other neonatal and parental characteristics and that of engraftment potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 32 publications
11
69
1
1
Order By: Relevance
“…These results are consistent with several previous studies showing that maternal age does not affect either nucleated cells or CD34 + cells (Donaldson et al 1999;Nakagawa et al 2004;George et al 2006;Mancinelli et al 2006). However, focusing on the 1-gravidae alone, the maternal age of 1-gravidae have a slightly positive correlation with the total LD cells (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are consistent with several previous studies showing that maternal age does not affect either nucleated cells or CD34 + cells (Donaldson et al 1999;Nakagawa et al 2004;George et al 2006;Mancinelli et al 2006). However, focusing on the 1-gravidae alone, the maternal age of 1-gravidae have a slightly positive correlation with the total LD cells (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…However, the multiple linear regression analyses in the present study show the significantly positive correlations between the total LD/CD34 + cells and maternal/neonatal factors (Table 3). These results are consistent with most of the previous reports (Donaldson et al 1999;Yamada et al 2000;Li et al 2001;George et al 2006;Mancinelli et al 2006), including that meconium in the amniotic fluid correlates with better cell counts (Askari et al 2005). Therefore the total LD cells per CB unit analyzed in the present study can be assumed as a substitute variable instead of the total nucleated cells in some previous studies (Lasky et al 2002;Mohyeddin Bonab et al 2004;Solves et al 2005), and can be also confirmed by other previous studies (Pafumi et al 2001;Bornstein et al 2005).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Many studies have shown that volume and TNC and progenitor counts are correlated. [6][7][8][9][10] Besides CBU cell content, a central issue of CB banking raised by many authors is HLA diversity. Indeed, the Bone Marrow Donors Worldwide collaboration of registries presents a lack of genetic diversity with an over-representation of donors from Northwestern European descent.…”
Section: Introductionmentioning
confidence: 99%
“…In France, qualification criteria are established by the Réseau Français du Sang Placentaire. The volume of the UCB has to be 470 mL and the TNCC 4140 × 10 7 . Many studies have shown that volume and TNC and progenitor counts are correlated.…”
Section: Introductionmentioning
confidence: 99%